2013
DOI: 10.3928/01913913-20121214-01
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Appearance in Patients With Down Syndrome

Abstract: To the Editors:Children with Down syndrome (DS) are commonly seen by pediatric ophthalmologists because signifi cant ocular conditions are associated with the disorder. 1 The presence of optic nerve anomalies has been noted in various small case series on children with DS. 2,3 We sought to determine the prevalence and character of optic nerve abnormalities among patients with DS in a large pediatric cohort and to ascertain whether patients with DS and optic nerve fi ndings suggestive of an intracranial proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
4
6
0
Order By: Relevance
“…Schneier et al showed that the incidence of ONHD was significantly higher in patients with Down syndrome [22]. In our study, the frequency of ONHD was higher in the children with Down syndrome than the value found in the normal population (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 45%
“…Schneier et al showed that the incidence of ONHD was significantly higher in patients with Down syndrome [22]. In our study, the frequency of ONHD was higher in the children with Down syndrome than the value found in the normal population (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 45%
“…Optic disc pallor was identified in only one child with Down syndrome in the present study, most likely representing a coincidental finding, similar to a few other cases reported previously (19, 20, 23). We did not identify any other sporadically described optic nerve anomalies in our subjects, such as morning glory (53, 54), optic nerve coloboma (55), optic nerve glioma (56), optic nerve atrophy (57) and optic nerve pit (24, 58).…”
Section: Discussionsupporting
confidence: 91%
“…We found that more children with Down syndrome had peripapillary atrophy (Figures 4E,H, 6C) and pigment anomalies (Figure 6); this was probably a consequence of the abnormal insertion of the disc onto the sclera. Tilted optic discs, peripapillary atrophy and scleral crescents have also been described in subjects with Down syndrome in other studies (3, 20, 23). Larger proportions of myopic crescents (13.2%) and tilted discs (8.1%) were previously reported in a population of adults with Down syndrome, along with a high prevalence of myopia (24).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our retrospective analysis confirms astigmatism as the prevailing refractive error as similarly described in previous studies [1][2][3][4][5][6][7][8][9][11][12][13]. Strabismus was recorded in more than one-third of our analyzed cohort; however, it is reported of variable frequency in the literature ranging from 22 to 57% as listed in Table 3.…”
Section: Discussionsupporting
confidence: 88%